Effect of President Trump s "Liberation Day" announcements on world stock markets: an event study approach - Espinosa-Mendez, C (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
This paper analyzes the global stock market response to the 2 April 2025, Liberation Day tariff announcement by President Trump. Employing an event study methodology, the study estimates abnormal returns (ARs) and cumulative abnormal returns (CARs) across different geographic regions and levels of trade exposure. The results reveal significant heterogeneity in market reactions: Europe, Asia, and Africa suffered the most pronounced losses, with countries classified as having intermediate trade exposure exhibiting more negative responses than those directly targeted by the policy.